PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN KAMPOENG DJOWO SEKATUL KABUPATEN KENDAL - Sebrica, Della; Suryoko, Sri; Prihartini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Costumer satisfaction is influenced by several factors, including the quality of service and price. This study establishes the service quality and price as a benchmark for customer satisfaction at Kampoeng Djowo Sekatul restaurant. This type of research is explanatory research, by using a self questionnaire administrator as the data collection technique. The tool used was a questionnaire. The population in this study is the food costumers Kampoeng Djowo Sekatul. Calculation of the sample using non-probability sampling technique, the type used is accidental sampling by respondents as many as 100 people. The data analysis technique used is the linear regression analysis. The conclusion from this study is that there are significant between service quality and price on consumer satisfaction Kampoeng Djowo Sekatul Kendal, partially affect service quality by 28.8% to customer satisfaction, and prices by 34.9% on customer satisfaction. Mutual influence the quality of service and price to customer satisfaction by 36.3%, while 63.7% is influenced by other factors. Advice: the company must conduct periodic evaluation and improvement of the quality of service that is better in the eyes of costumers, Kampoeng Djowo Sekatul restaurant must still maintain a decent price for the costumer based on their level of income, a place of comfort and quality of food as well as other competitors.